2020
DOI: 10.5267/j.msl.2019.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting customers selection of community pharmacies: The mediating effect of branded pharmacies and the moderating effect of demographics

Abstract: This research aims to identify and evaluate different factors influencing the customer decision in selecting a community pharmacy in the city of Amman, and study the possible impact of branded pharmacy on the selection process. Five main factors were selected based on the literature review, including convenience, physical environment, sales promotions, qualified and experienced pharmacists and customer service and three main hypotheses and twelve sub-hypotheses were developed. A descriptive analytical methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Table 4 presented the results of the Harman's Test for the deduction of common method bias. Hence, the result of the mediation analysis revealed that reliability, trust and loyalty are the major mediators or deciding variables regarding the medical practitioners' sensitivity towards their selection of surgical instruments (Ghattas and Al-Abdallah, 2020). Thus, trust, reliability and loyalty had a higher impact on the medical practitioners' sensitivity while selecting the particular surgical instrument brand (Pandey et al , 2019).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Table 4 presented the results of the Harman's Test for the deduction of common method bias. Hence, the result of the mediation analysis revealed that reliability, trust and loyalty are the major mediators or deciding variables regarding the medical practitioners' sensitivity towards their selection of surgical instruments (Ghattas and Al-Abdallah, 2020). Thus, trust, reliability and loyalty had a higher impact on the medical practitioners' sensitivity while selecting the particular surgical instrument brand (Pandey et al , 2019).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Mahmoud and Mahmoud (2016) specified pharmacy location, technical quality (including courtesy and respect shown by the pharmacy staff) and pharmacist competency in explaining drug use instructions as the most influential satisfaction factors. Ghattas and Al-Abdallah (2020) stated that connivance, qualified and experienced pharmacists and customer service are decisive factors in selecting community pharmacies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current competitive marketing environment obliges community pharmacies to develop business improvements to maintain their patronage and enhance their performance (Abdallah et al , 2017; Ghattas and Al-Abdallah, 2020). Therefore, community pharmacies hoping to prosper must recognize the importance of patient trust and loyalty (Castaldo et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, anecdotal industry data reveals that only 16% of customers entering a pharmacy see themselves as "patients" (Stochasis, 2021) while recently pharmaciesas retail outletsare receiving growing academic attention (e.g. Dung, 2019;Ghattas and Al-Abdallah, 2020;Glaveli et al, 2020;Grew et al, 2020;Habash and Al-Dmour, 2020). The importance thus of adopting a customer perspective rather than a patient one is highlighted by both academics and practitioners (Schork, 2015;Deloitte, 2020).…”
Section: Introductionmentioning
confidence: 99%